A novel truncating variant of SPAST associated with hereditary spastic paraplegia indicates a haploinsufficiency pathogenic mechanism - Nan, Haitian; Chu, Min; Liu, Li; Xie, Kexin; Wu, Liyong (Frontiers in Neurology, 2022)
Introduction: Hereditary spastic paraplegias (HSPs) are genetic neurodegenerative diseases. The most common form of pure HSP that is inherited in an autosomal dominant manner is spastic paraplegia type 4 (SPG4), which is caused by mutations in the SPAST gene. Different theories have been proposed as the mechanism underlying SPAST-HSP for different types of genetic mutations, including gain- and loss-of-function mechanisms. To better understand the mutation mechanisms, we performed genetic analysis and investigated a truncating SPAST variant that segregated with disease in one family. Objectives and Methods: We described a pure HSP pedigree with family members across four generations. We performed genetic analysis and investigated a novel frameshift pathogenic variant (c.862_863dupAC, p. H289Lfs*27) in this family. We performed reverse transcription-polymerase chain reaction (RT-PCR), Sanger sequencing, and quantitative RT-PCR using total RNA from an Epstein-Barr virus-induced lymphoblastoid cell line produced from the proband. We also performed Western blotting on cell lysates to investigate if the protein expression of spastin is affected by this variant. Results: This variant (c.862_863dupAC, p. H289Lfs*27) co-segregated with pure HSP in this family and is not registered in any public database. Measurement of SPAST transcripts in lymphoblasts from the proband demonstrated a reduction of SPAST transcript levels through likely nonsense-mediated mRNA decay. Immunoblot analyses demonstrated a reduction of spastin protein expression levels in lymphoblasts. Conclusion: We report an SPG4 family with a novel heterozygous frameshift variant p.H289Lfs*27 in SPAST. Our study implies haploinsufficiency as the pathogenic mechanism for this variant and expands the known mutation spectrum of SPAST.